Method of Sewage Sludge Dewatering with the Use of GEOTUBE Technology Elements at the Bortnichy Aeration Station - Kashkovsky, V.I.; Yevdokymenko, V.O.; Kamenskyh, D.S.; Yevdokymenko, A.N. (Science and Innovation, 2024)
The research deals with major environmental and social problem, dehydration of sewage sludge with the help of GeoTube technique elements. Dehydration process of sludge of different origin has been developed. A pilot installation has been designed and produced. This installation is realized as a filter module placed in the tank of Bortnichy’s sewage treatment plant where the aerobically-stabilized sludge treated with flocculant Praestol 859 BS and water from filtration fields are delivered to. It can be used for reduction of workload on sludge fields, as well as for purification of supernatant water and dewatering of accumulated sludge.